ON TRANSLATING TITLES IN ARTISTIC DISCOURSE - Boyko, Lyudmila (Vertimo studijos, 2017)
As a specific type of proper names, the titles of works of art constitute a very important and highly translation-sensitive element of art discourse. This paper aims to demonstrante how specific titling in arts affects the translation process. To that end, a brief overview of the title’s role in verbal and non-verbal discourse is given. Further on, it is shown how, due to the involvement of heterogenic semiotic codes, specific functioning of titles results in a different perception strategy, making most routine title translation strategies inapplicable. The paper concludes that the choice of translation strategy is determined by various extra-linguistic factors, such as alternative titling, back-translation situations, and the requirements of the commissioner.